The advantages and limitations of biophysical modelling as a tool for informing limit setting in New Zealand's barrier‐enclosed estuaries - Karin R. Bryan; Benjamin T. Stewart; Alex M. Port; Hannah F. E. Jones; Conrad A. Pilditch (New Zealand Journal of Marine and Freshwater Research, 2022)
Estuaries are the receiving environment for catchment‐derived contaminants, the fate of which depends on the interplay between the estuarine geomorphology and hydrodynamics. In large estuaries, biophysical processes are spatially and temporally‐diverse, which makes understanding and managing the impact of human activities challenging. Here we use two common modelling approaches to explore the advantages and limitations of biophysical modelling as a tool for limit setting in a large barrier‐enclosed estuary in New Zealand. The model shows the large spatial variation in water quality associated with low upper harbour flushing. Variations can also be attributed to spatial variation in processes (such as denitrification). Although the non‐linear interactions between processes within these models can limit the value of using specific detail of outputs for decision making, the general patterns and sensitivities can be used to define areas, explore connectivity, and provide some information when monitoring data is lacking. Even in a deterministic modelling environment, it can very difficult to attribute water quality variations output at one location to the loading that caused these variations. While biophysical modelling will likely remain a core tool for informing management, any future development of limit setting methods for estuaries should recognise the inherent constraints we describe here.